2011
DOI: 10.4161/cib.4.2.14381
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila infection is enhanced in a RacH-null mutant of Dictyostelium

Abstract: Recently we reported that Dictyostelium cells ingest Legionella pneumophila by macropinocytosis, whereas other bacteria, such as Escherichia coli, Mycobacterium avium, Neisseria meningitidis or Salmonella typhimurium, are taken up by phagocytosis.1 In contrast to phagocytosis, macropinocytosis is partially inhibited by PI3K or PTEN inactivation, whereas both processes are sensitive to PLC inhibition. Independently from reduced uptake, L. pneumophila proliferates more efficiently in PI3K-null than in wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Only a handful of bacteria strains are not phagocytosed, but very few systematic studies have been published in this regard. Legionella pneumophila is taken up by macropinocytosis, thus its uptake by natural wild type strains is negligible (Peracino et al, 2010; Balest et al, 2011). Bacillus anthracis was reported not to be phagocytosed (Depraitere and Darmon, 1978), but a recent report described its uptake, though no details were offered on the efficiency of phagocytosis (Nasser et al, 2013).…”
Section: Dictyostelium: Professional Phagocyte and Pathogen Hostmentioning
confidence: 99%
“…Only a handful of bacteria strains are not phagocytosed, but very few systematic studies have been published in this regard. Legionella pneumophila is taken up by macropinocytosis, thus its uptake by natural wild type strains is negligible (Peracino et al, 2010; Balest et al, 2011). Bacillus anthracis was reported not to be phagocytosed (Depraitere and Darmon, 1978), but a recent report described its uptake, though no details were offered on the efficiency of phagocytosis (Nasser et al, 2013).…”
Section: Dictyostelium: Professional Phagocyte and Pathogen Hostmentioning
confidence: 99%
“…To test this hypothesis, we used a RacH‐ Dictyostelium strain whose vesicle trafficking is disrupted due to defective acidification of early endosomes. This impairs macropinocytosis and chemotaxis (Somesh et al , 2006; Balest et al , 2011) As shown in Fig 4G, whereas a back‐to‐front gradient in PI(3,4)P2 membrane association was apparent in wild‐type Dictyostelium AX2 cells, in the RacH‐ cells “back” regions were weaker and there were more cytosolic PI(3,4)P2‐enriched vesicles. Line scans of pixel intensity across wild‐type or mutant cells confirmed greater PI(3,4)P2 accumulation at the back of wild‐type cells (Fig 4H).…”
Section: Resultsmentioning
confidence: 95%
“…Somesh et al, 2006;Balest et al, 2011) As shown in Fig 4G, whereas a back-to-front gradient in PI(3,4)P2 membrane association was apparent in wild-type Dictyostelium AX2 cells, in the RacHcells "back" regions were weaker and there were more cytosolic PI(3,4)P2-enriched vesicles. Line scans of pixel intensity across wild-type or mutant cells confirmed greater PI(3,4)P2 accumulation at the back of wild-type cells (Fig 4H).…”
mentioning
confidence: 70%
“…Therefore, it has been proposed that RacH acts as a regulator of vesicle sorting. Furthermore, RacH also plays an important role in host–pathogen interactions, as it was shown that racH -null cells are more susceptible to infection by Mycobacterium marinum or Legionella pneumophila : the bacteria proliferate more easily in racH -null cells, which was attributed to a defect in endosome acidification [ 302 , 303 ]. On the other hand, the depletion of RacH has a deteriorating impact on bacterial transmission between Dictyostelium cells, since the release of bacteria from racH -null cells is almost completely abrogated [ 303 ].…”
Section: Comparative Analysis Of the Rho Signalling In Dictyostelium And Mammalian Cellsmentioning
confidence: 99%